Effectiveness of the My ADA Application on ANC Visiting Behaviour of Pregnant Women in the Cities of Bengkulu and Cilandak, South Jakarta - Yuniarti Yuniarti; Elvi Destariyani; Erlin Puspita; Nurhayati Nurhayati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Antenatal care (ANC) is a medical service that expectant mothers get from qualified personnel. In the current era of digitization, apps are extremely required since they may make things simpler. ANC results are often entered in the KIA book, but recording is still done by hand, and pregnant women frequently forget to bring the KIA book. The purpose of this study is to evaluate the application's efficacy. My ADA on the ANC visitation patterns of expectant mothers in South Jakarta's Bengkulu and Cilandak cities. This kind of quantitative study employs a control group design in a quasi-experimental setting. The study will be conducted in Cilandak, South Jakarta, and PMB Bengkulu City. In 2023, there were 6,279 pregnant women in the PMB neighborhood of Bengkulu City, Cilandak, South Jakarta; 106 of them were selected using the purposive sampling approach. Pregnant women's average knowledge of ANC increased in the intervention group using the My ADA application compared to the control group using the KIA book. The intervention group's knowledge increased with a p-value of 0.000 <0.05, indicating that the My ADA application had an impact on pregnant women's knowledge, while the intervention group's p-value of 0.000 <0.05 indicated that the KIA book had an impact on pregnant women's knowledge of ANC in South Jakarta. The Mann-Whitney test results showed that Mean P-Value = 0.000, there is a difference in the average knowledge score between the My ADA application group and the KIA book group, so it can be concluded that the My ADA Application is more effective in increasing pregnant women's knowledge about ANC compared to KIA book. Keyword: Application, Attitude, Knowledge , Pregnant